استراتيجيتنا التحسين والتقبيح في الخطاب النقدي تطبيقا على الخطابين القرآني والشعري: مقاربة ومصفية تحليلية - مختار، عز الدين علي (جامعة أم درمان الأهلية - كلية الآداب, 2022)
إن أهمية هذا البحث تنبع من كونه يتناول استراتيجيتي التحسين والتقبيح في الخطاب القرآني والخطاب الشعري؛ ليتعرف التقنيات الفنية الموظفة في التعبير بهاتين الاستراتيجيتين على مستوى البنية والوظيفة معا في هذين الخطابين. وقد اقتضت طبيعة هذا البحث أن يؤطر تأطيرين: نظري وإجرائي بحيث يحوي كل منهما عناوين جانبية موضحة كانت في التأطير النظري: مفهوم التحسين والتقبيح، ومستوياتهما، وما يقعان عليه، وركائزهما، ودواعيهما، وأهما استراتيجيتان أم وظيفتان؟، وكانت في التأطير الإجرائي الخطاب القرآني والخطاب الشعري وتحت كل منهما النصوص المختارة التي تمثل مستويات التحسين والتقبيح. وأما المنهج الذي وقع عليه الاختيار في مقاربة هذا الموضوع فهو المنهج الوصفي التحليلي الذي يعين على فحص النصوص المختارة من الداخل بنية ووظيفة. لقد تمخض البحث عن نتائج لعل من أهمها أن مستويي تجميل القبيح وتقبيح الجميل يعملان على تخييب أفق انتظار المتلقي وتوقعه، في حين أن مستويي تجميل الجميل وتقبيح القبيح يعمدان إلى تأكيده، وأن استراتيجية التجميل والتقبيح ليست وظيفة أو غاية بل هي وسيلة لتحقيق وظيفتين: جمالية أو شعرية تتصل بالبنية، ونفسية إيحائية تتصل بالمتلقي ترغيبا أو تنفيرا. ومن أهم التوصيات التي يمكن أن تذكر في هذا الصدد هو أن تدرس هاتان الاستراتيجيتان في الخطاب الروائي. The importance of this research stems from the fact that it deals with the strategies of beautification and uglification in the Qur’anic and poetic discourses, in order to identify the techniques employed in expressing these two strategies at the level of both form and function in these two types of discourses. The nature of this research required the employment of two frameworks: theoretical and procedural, and each of them contained elucidating subheadings. Those in the theoretical framework included: the concepts of beautification and uglification, their levels, the texts they are applied on, their pillars and their motives, and whether they should be considered as strategies or functions. On the other hand, the subheadings in the procedural framework included Qur’anic discourse and poetic discourse and under each of them the selected texts that represent the levels of beautification and uglification were included. As for the method that was chosen in approaching this topic, it is the descriptive-analytical method, which helps in examining the selected texts from within their form and function. The research has yielded some results, perhaps the most important of which is that the levels of beautifying the ugly and uglifying the beautiful tend to disappoint the prospect of the recipient’s expectations, whereas the levels of beautifying the beautiful and uglifying the ugly tend to assure it. Furthermore, the results showed that the strategy of beautification or uglification is not a function or an end in itself, but rather a means to achieve two functions: an aesthetic/poetic function related to the form and a psychological evocative function related to the recipient in terms of encouragement or discouragement. One of the most important recommendations that can be mentioned in this regard is to study these two strategies in the narrative discourse.
Keywords: الخطاب الشعري -- الوسائل الفنية -- النصوص القرآنية -- البنية اللغوية